Identity, place narrative and biophilic urban development: Connecting the past, present and future for sustainable liveable cities - O'Sullivan, Kate; Shirani, Fiona; Hale, Rachel; Pidgeon, Nick; Henwood, Karen (Frontiers in Sustainable Cities, 2023)
Urbanisation presents sustainability challenges for the natural environment, resources and ecological systems, whilst high levels of pollution and disconnect from the natural environment can adversely impact the health and wellbeing of urban residents. Rapid urbanisation can also curtail processes of placemaking, including place attachment and place identity, raising questions around the social sustainability and livability of cities into the future. With such concerns in mind, cities are increasingly called upon to develop in ways that are environmentally, socially, and economically sustainable. Biophilic urbanism and biophilic design offer an approach to sustainable urban development. Such approaches propose incorporation of nature and green infrastructure within the city in order to positively affect human health and wellbeing, in addition to benefiting environmental, social and economic sustainability. This paper explores findings from community focus groups exploring perceptions of a proposed biophilic urban development in Wales, UK. Our research explored how community members understood and negotiated possible impacts of the development on the social, environmental and economic landscape of the city by drawing on their own emplaced experiences. Through gaining an understanding of community place identity and narrative as well as distinctive and defining place characteristics, connections and synergies are revealed between place-based attachment and principles of biophilia. This in turn can provide a trajectory of place transformation authentic to both community and place identity and which supports the aims of biophilic design. As a consequence, it is possible for biophilic design to not only be sustained by communities, but to become an integral element of place identity and place attachment, contributing to the sustainability of place through time.